Synergistic Catalysts of the Region’s Entrepreneurial Potential Realization in Conditions of Ukraine’s Integration into the European Union - Chaikina, Alina; Chaikina, Nataliia; Zerniuk, Olena; Frolina, Kateryna (International Journal of Engineering and Technology, 2018)
In the article theoretical approach of the region entrepreneurial potential identification was proposed. As well authors suggested a base structure of the region entrepreneurial potential. Analyse of entrepreneurial activity in Ukraine was done and it was showed that small and medium-sized enterprises do not have strong state and regional support and that is why their position on market is changeable and occurs on their profitable activity. Authors defined catalysts that influence on the level of the entrepreneurial potential realization and prescribed their synergistic influence. Also methodical approach that helps to identify the realization level the entrepreneurial potential of each region was proposed. Psychological aspects of entrepreneurial potential was determined and investigated.Â